Effects of Audiovisual Education on Community Knowledge of Snakebite Management - Anggraini, Novita Ana; Afiani, Nurma; Ambarika, Rahmania; Fauziah, Wardah; Haryani, Mukti Sri (Journal of Applied Nursing and Health, 2025)
Background: Snakebites are an emergency that can cause death if not treated immediately. Lack of community knowledge on first aid for snakebites can increase the incidence of infection or death. Education is needed to improve community knowledge. However, community education using audiovisual methods for snakebite prevention remains limited. The purpose of this study was to analyze the effects of audiovisual education on knowledge of handling snakebites in the community at UPT Puskesmas Kepanjenkidul, Blitar City. Methods: A quasi-experimental one-group pre–posttest design was used. Participants were ≥18 years old community members recruited from the outpatient registry using simple random sampling. A validated 15-item knowledge questionnaire was administered before and after a 5-minute audiovisual educational intervention. Inclusion criteria: consent to participate; exclusion: prior training on snakebite management. Data was collected using a knowledge questionnaire used to assess community knowledge regarding snakebite management. The study reporting followed the TREND Statement for non-randomized evaluations of behavioral interventions. Data were analyzed using the Wilcoxon rank test with α < 0.05.. Results: The level of knowledge of handling snakebites before education was in the fair category for most of the respondents (45 respondents or 51.1%). After education, almost all respondents (80 respondents or 90.9%) had a good level of knowledge. Results of the Wilcoxon test showed a p < 0.001. Conclusion: Health education using audiovisual media influences knowledge of handling snakebites. Audiovisual media can display elements of images and sound simultaneously in conveying information. Video media in the learning process is more effective in increasing knowledge. Thus, health workers are expected to provide education using audiovisual media since it is easy to receive and understand by the community.